PENGARUH LATIHAN PLYOMATRIC (KNEE TUCK JUMP) TERHADAP PADA TIM BOLA VOLI PUTRA GIRI PEKANBARU - Muhammad Sopianuddin; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: The problem in this study take the lack of leap in samash, this can be seen by anyone sharing the observations and interviews to coach the team volleyball men’s giri pekanbaru for training and this is one factor causes of defeat.what kind of this study is the kind of research experiments to see the influence of the from of exercis. The purpose of this research it is to know the impact of training plyometric ( knee tuck jump ) to muscle powor the muscles of limbs on the team vollyball men’s giri pekanbaru, amounting to 10. The sempling is to use the total sampilng. Where is the total population in the spotlinght on the sampel. The data interieval of preetest and long jump as a tool to measure powor limb muscles. The analysis carried out by using uji- T. Based on analysis the data and discussion, it can be concluded that there is a significant influence of the exercises plyometric ( knee tuck jump ) to power the muscles of limbs on the team volleyball men’s giri pekanbaru proven with T count of 10 .75 and T tebel 1,833 that T with>n’t the tebel. In the standard of a= 0,05Keywords: The Plyometric (Knee Tuck Jump), Power the muscles of limbs.